2017
DOI: 10.1002/2017ef000554
|View full text |Cite
|
Sign up to set email alerts
|

Slowdown of global surface air temperature increase and acceleration of ice melting

Abstract: Although recent decades have been the warmest since 1850, and global mean temperatures during 2015 and 2016 beat all instrumental records, the rate of increase in global surface air temperature (GSAT) significantly decreased at the beginning of the 21st Century. In this context, we examine the roles of ice melting and associated increase in sea‐water mass, both of which significantly increased at the same time as GSAT decreased. Specifically, we show that (1) the slowdown of the rate of increase in GSAT betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…Therefore, the 1:1 ratio of energy going into the ocean and melting grounded ice has to be regarded as an average over the whole last glacial transition and cannot be expected to hold for the anthropogenic warming. However, as a recent study has shown 28 , including ice melting is important to close also the current global energy budget and can provide new insights into the mechanism behind recent decadal global temperature variabilities.…”
Section: Article Researchmentioning
confidence: 99%
“…Therefore, the 1:1 ratio of energy going into the ocean and melting grounded ice has to be regarded as an average over the whole last glacial transition and cannot be expected to hold for the anthropogenic warming. However, as a recent study has shown 28 , including ice melting is important to close also the current global energy budget and can provide new insights into the mechanism behind recent decadal global temperature variabilities.…”
Section: Article Researchmentioning
confidence: 99%
“…Globally, despite continuing increase in atmospheric CO 2 concentration, there has been a recent slowdown in the rate of warming. This may be due to a redistribution of heat within the atmosphere-cryosphere system ( 15 ), with the reduction in atmospheric heating almost equating in energy terms to the contemporaneous increases in ice melting.…”
Section: Introduction – Climate Change In Antarcticamentioning
confidence: 99%
“…It should be noted that residual global ice volume might have been higher during MIS 19 than MIS 1 (Elderfield et al 2012;Regattieri et al 2019;Vavrus et al 2018). This may have increased climate sensitivity during MIS 19 given the nonlinear relationship between astronomical forcing and ice volume during the Quaternary (Past Interglacials Working Group of PAGES 2016) and the fact that polar ice volume provides one of the most important feedback mechanisms in the climate response to radiative forcing (Berger et al 2017;Westerhold et al 2020).…”
Section: The Climatic Evolution Of Mis 19mentioning
confidence: 99%